Factors affecting sperm recovery rates and survival after centrifugation of equine semen - Ferrer, Maria S.; Lyle, S. K.; Eilts, B. E.; Eljarrah, A. H.; Paccamonti, D. L. (My University, 2012)
Conventional centrifugation protocols result in important sperm losses during removal of the supernatant. In this study, the effect of centrifugation force (400 or 900 × g), duration (5 or 10 min), and column height (20 or 40 mL; Experiment 1); sperm concentration (25, 50, and 100 × 10[superscript 6]/mL; Experiment 2), and centrifugation medium (EZ-Mixin CST [Animal Reproduction Systems, Chino, CA, USA], INRA96 [IMV Technologies, Maple Grove, MN, USA], or VMDZ [Partnar Animal Health, Port Huron, MI, USA]; Experiment 3) on sperm recovery and survival after centrifugation and cooling and storage were evaluated. Overall, sperm survival was not affected by the combination of centrifugation protocol and cooling. Total sperm yield was highest after centrifugation for 10 min at 400 × g in 20-mL columns (95.6 ± 5%, mean ± SD) or 900 × g in 20-mL (99.2 ± 0.8%) or 40-mL (91.4 ± 4.5%) columns, and at 900 × g for 5 min in 20-mL columns (93.8 ± 8.9%; P < 0.0001). Total (TMY) and progressively motile sperm yield followed a similar pattern (P < 0.0001). Sperm yields were not significantly different among samples centrifuged at various sperm concentrations. However, centrifugation at 100 × 10[superscript 6]/mL resulted in significantly lower total sperm yield (83.8 ± 10.7%) and TMY (81.7 ± 6.8%) compared with noncentrifuged semen. Centrifugation in VMDZ resulted in significantly lower TMY (69.3 ± 22.6%), progressively motile sperm yield (63.5 ± 18.2%), viable yield (60.9 ± 36.5%), and survival of progressively motile sperm after cooling (21 ± 10.8%) compared with noncentrifuged semen. In conclusion, centrifuging volumes of ≤ 20 mL minimized sperm losses with conventional protocols. With 40-mL columns, it may be recommended to increase the centrifugal force to 900 × g for 10 min and dilute the semen to a sperm concentration of 25 to 50 × 10[superscript 6]/mL in a milk- or fractionated milk-based medium. The semen extender VMDZ did not seem well suited for centrifugation of equine semen.
Keywords: Centrifugation; Stallion semen; Semen; Semen viability; Recovery; Horse